Nieodpowiedzialność i odpowiedzialność w aspektach teorii prawa: [Irresponsibility and responsibility in the theory of law] (Studia Prawnicze / The Legal Studies, 1985)
The author suggests to introduce a category of irresponsibility into the science of law. Irresponsibility has been so far considered a moral category and the relationship between the lack of responsibility and law has not been stressed.The author analyzed various types of legal responsibility and showed that the system of responsibility corresponds to social norms. The author refuses to include administrative norms set by the state into the notion of a legal norm. He thinks they are an element in a general system of organizational norms.The separation of administrative norms set by the state allows to show the specificity of responsibility and irresponsibility which is connected with them.